ANALISIS DAMPAK PENGGUNAAN MEDIA SOSIAL INSTAGRAM DALAM MENINGKATKAN PENJUALAN PRODUK PAKAIAN PADA TOKO XYZ SAMARINDA - Shafira Nur Azizah (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
The purpose of this research is to find out how the Impact Analysis of Using Social Media is in identifying factors that influence the success of marketing via Instagram to increase sales of clothing products at the XYZ Samarinda Store. This type of research is descriptive qualitative. Data collection was carried out using observational research, interviews and documentation. Data analysis was carried out by collecting data, condensing data, presenting data and drawing conclusions. The research results show that the use of Instagram social media at the XYZ Samarinda store has not had a significant impact in increasing clothing sales. Some of the obstacles faced include less than optimal account management, differences in marketing preferences between shop owners and management, and online inactivity. However, the support of loyal customers and direct interaction in traditional sales helps the store's success, with traditional sales remaining effective in the local market despite the growing online trend. Overall, the Samarinda XYZ store relies more on traditional sales methods and customer service to remain competitive.